Uma análise do campo cinematográfico brasileiro sob a perspectiva industrial - Cesário, Lia Bahia (2009)
The theme of this work is the relation between culture and industry in Brazil, departing from the analysis of the dynamics of the Brazilian cinematographic field. The research focuses on the relationship between Brazilian state and the industrialization of Brazilian cinema during the years 2000. A new reading of the main historical milestones of the industrialization of national cinema supports the creation of an adequate frame to understand the patterns of state intervention in the cinematographic field. With such referential, we explore the connections and disconnections among discourses, practices and regulatory policies towards the Brazilian audiovisual in globalization times. The preservation of the distinction places in the audiovisual media derives not only from the incoherence between discourses and practices but also from an incomplete process of institutionalization of the state intervention. However, we cannot affirm that Brazil remained immune to the tendency of blurred frontiers in audiovisual media. The experience of Globo Filmes, driven by private interests, puts in evidence the potentiality for transit between cinema and television and vice-versa. Thus, the irregularities in state intervention gave room to the rise of attempts to make a Brazilian audiovisual industry feasible, but not to a state policy of permanent building of mediations between culture and economy